Single spin universal Boolean logic gate - Agarwal H.; Pramanik S.; Bandyopadhyay S. (My University, 2025)
Recent advances in manipulating single electron spins in quantum dots have brought us close to the realization of classical logic gates, where binary bits are encoded in spin polarizations of single electrons. Here, we show that a linear array of three quantum dots, each containing a single spin polarized electron, and with nearest neighbor exchange coupling, acts as a NAND gate. The energy dissipated during switching this gate is the Landauer-Shannon limit of kTln(1/pi) (T = ambient temperature and pi = intrinsic gate error probability). With present day technology, pi = 10 -9 is achievable above 1K temperature. Even with this small intrinsic error probability, the energy dissipated during switching is only ∼21kT while today's nanoscale transistors dissipate about 40 000-50 000kT when they switch. © IOP Publishing Ltd and Deutsche Physikalische Gesellschaft.